An experimental study of flow induced vibration of a flexible model riser - Lu, J.; Do, Khac Duc; Pan, J. (The Australian Acoustical Society, 2013)
This paper experimentally identifies some non-linear effects, e.g. modal coupling effect and beating motion, on a flexible model riser due to variable curvature when vortex-induced vibration (VIV) occurs. The VIV on the riser can cause enlarging dynamic stress of the body and reducing its fatigure life. This work expands existing numerical and analytical investigations on a model riser with constant curvature in shear flow condition. The results indicate that for a flexible model riser displaced in non-uniform shear flow when VIV occurred, the curvature shows substantial effects on lock-in response and multi-mode non-lock-in response. The modal coupling effect on lock-in response repeats the same effect on the structure in air, which indicates that modal coupling effect seems independent to the locking phenomenon. This experimental investigation embeds the situation when displacing a flexible rubber cable with initial caterany shape stretching its bottom end to most tensioned straight condition for varying the curvature. The effect of varying curvature on the vibration characteristics of the rubber cable is identified when displaced in air. The same effect on the structure when vortex-induced vibration occurred is taken into account through a fan produced wind loading.